Which types of anti-smoking television advertisements work better in Taiwan? - Huang, Li-Ling (Health Promot Int, 2018)
Research in high income countries suggests that anti-smoking television advertisements with emotionally evocative graphic messages or personal testimonials that depict serious consequences from smoking are the most effective. Research to determine the most effective smoking cessation messages for low- and middle-income countries is needed to inform campaign development in these countries. Fifty-four male Taiwanese smokers, aged 18–34, rated advertisements and participated in a focus group to evaluate eight antismoking television advertisements with contrasting messaging strategies. Participants individually evaluated advertisements, after which they participated in a semi-structured focus group discussion (10 groups, 2–9 smokers per group). One week after this session, participants were called to assess advertisement recall. Both quantitative and qualitative data indicated that highly emotional testimonial ads that featured a graphic portrayal of personal suffering from the consequences of smoking and visceral graphic ads were more effective. The ad on tobacco industry denormalization that focuses on the responsibility of the industry for smoking-related harms was considered ineffective because smokers perceived it as having little personal relevance. Humorous advertisements were evaluated as the least effective because they lacked strong emotional content linked to smoking consequences. Qualitative results suggest that advertisement characteristics are more important than the demographic characteristics of people featured in advertisements. Study findings provide preliminary evidence that testimonial ads that involve graphic and emotionally evocative portrayals of smoking-attributed diseases and visceral graphic ads may have the greater potential to motivate Taiwanese smokers to quit smoking.